1H relaxation and dynamics of triphenylbismuth in deuterated solvents. (18th April 2019) - Kruk, Danuta; Masiewicz, Elzbieta; Umut, Evrim; Scharfetter, Hermann
ABSTRACT: 1 H spin–lattice relaxation experiments have been performed for triphenylbismuth dissolved in fully deuterated glycerol and tetrahydrofuran. The experiments have been carried out in a broad frequency range, from 10 kHz to 40 MHz, versus temperature. The data have been analysed in terms of a relaxation model including two relaxation pathways: 1 H- 1 H dipole–dipole interactions between intrinsic protons of triphenylbismuth molecule and 1 H- 2 H dipole–dipole interactions between the solvent and solute molecules. As a result of the analysis, rotational correlation times of triphenylbismuth molecules in the solutions and relative translational diffusion coefficient between the solvent and solute molecules have been determined. Moreover, the role of the intramolecular 1 H- 1 H relaxation contribution has been revealed, depending on the motional parameters, as a result of decomposing the overall relaxation dispersion profile into contributions associated with the 1 H- 1 H and 1 H- 2 H relaxation pathways. The possibility of accessing the contribution of the relaxation of the intrinsic protons is important from the perspective of exploiting Quadrupole Relaxation Enhancement effects as possible contrast mechanisms for Magnetic Resonance Imaging. GRAPHICAL ABSTRACT: